Attitudes of Employees to Intrafirm Interaction in the Sphere of Social and Labor Relations - Наталья Дмитриевна Воронина; Ирина Казбековна Зангиева (Journal of Economic Sociology, 2011)
The article is devoted to employees’ orientations within the space of «cooperation−conflict». Social attitudes of employees to interactions between main actors of labor relations are empirically studied by instruments of factor analysis.